Answer:
Step-by-step explanation:
Since this is not factorable, let's just complete the square:
![x^2+6x=19\\x^2+6x+9=28\\(x+3)^2=28\\x+3=\sqrt{28}\\x=2\sqrt{7}-3](https://tex.z-dn.net/?f=x%5E2%2B6x%3D19%5C%5Cx%5E2%2B6x%2B9%3D28%5C%5C%28x%2B3%29%5E2%3D28%5C%5Cx%2B3%3D%5Csqrt%7B28%7D%5C%5Cx%3D2%5Csqrt%7B7%7D-3)
the answer is 1 and 4
Start by subtracting, so on #1 subtract 5-8, 8-11, 11-14
then go up to x, -2--1, -1-0, 0-1
Answer:
third number = 4,
equation of y, y = 5x - 11
equation of n, n = 4x
equation of x, n + x + y =19
Step-by-step explanation:
so lets write evertything as a n equation. n + x + y =19. N is the first number, x is the second number, and y is the third number. We will write the equation for y as follows 5x - 11. N will be four times the second number, so 4x. If substitute the values for out equation for x we will find what x equals to. So (4x) + x + (5x - 11) = 19
10x = 30
x = 3.
Then you substiute the answer for x in the equation for y. This will get you 5(3) - 11
15 - 11
4 = third number